The Effect of Feeding Native Grass, Jackfruit Leaves and Leguminosa on Daily Weight Increase and Body Sizes of Goats - Salim, Muhammad Ade; Hariyono, Dwi (Faculty of Animal Science, Universitas Brawijaya, 2024)
The use of foliage and legumes in goat diet is essential to serve protein sources for maintenance and productivity. This study aimed to evaluate the effect of providing native grass, jackfruit leaves (Artocarpus heterophyllus), and different legumes such as Leucaena leucocephala and Asystasia gangetica (L.) T. Anderson on average daily gain (ADG) and weekly increased body measurements) of four female Kacang goats (5-7 months old; average body weight 6.98?± 1.44 kg) kept in individual pens (1 m x 1.2 m × 1.2m (length x width x height) with a soil base. A 4 x 4 latin square design with four treatments: T0 (100% natural grass), T1 (100% lamtoro leaves), T2 (100% jackfruit leaves), and T3 (100% spinach) were used. The data obtained were analyzed using analysis of variance. The results showed that feeding goats with different type of forages had a significant effect (P<0.05) on ADG, in which the goats fed jackfruit leaves showed the highest ADG value (142.85 ± 15.43 gr/head/day) (p<0.05). Meanwhile, the ADG of goats fed native grass, L. leucocephala, and A. gangetica leaves were not significantly different (P>0.05). The results also showed that different forages had no significant effect (P>0.05) on the weekly increase in body size measurements, including body length, shoulder height and chest girth. It can be concluded that giving jackfruit leaves can increase the ADG of Kacang goats. The use of jackfruit leaves solely can be recommended to increase the growth of goats.